Highly electrostrictive salt cocrystal and the piezoelectric nanogenerator application of its 3D-printed polymer composite - Sahoo, Supriya; Panday, Rishukumar; Kothavade, Premkumar; Sharma, Vijay Bhan; Sowmiyanarayanan, Anirudh; Praveenkumar, Balu; Zareba, Jan K.; Kabra, Dinesh; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (ACS Applied Materials and Interfaces, 2024)
Ionic cocrystals with hydrogen bonding can form exciting materials with enhanced optical and electronic properties. We present a highly moisture-stable ammonium salt cocrystal [CH3C6H4CH(CH3)NH2][CH3C6H4CH(CH3)NH3][PF6] ((p-TEA)(p-TEAH)PF6) crystallizing in the polar monoclinic C2 space group. The asymmetry in (p-TEA)(p-TEAH)PF6 was induced by its chiral substituents, while the polar order and structural stability were achieved by using the octahedral PF6- anion and the consequent formation of salt cocrystal. The ferroelectric properties of (p-TEA)(p-TEAH)PF6 were confirmed through P-E loop measurements. Piezoresponse force microscopy (PFM) enabled the visualization of its domain structure with characteristic ``butterfly'' and hysteresis loops associated with ferro- and piezoelectric properties. Notably, (p-TEA)(p-TEAH)PF6 exhibits a large electrostrictive coefficient (Q(33)) value of 2.02 m(4) C-2, higher than those found for ceramic-based materials and comparable to that of polyvinylidene difluoride. Furthermore, the composite films of (p-TEA)(p-TEAH)PF6 with polycaprolactone (PCL) polymer and its gyroid-shaped 3D-printed composite scaled-up device, 3DP-Gy, were prepared and evaluated for piezoelectric energy-harvesting functionality. A high output voltage of 22.8 V and a power density of 118.5 mu W cm(-3) have been recorded for the 3DP-Gy device. Remarkably, no loss in voltage outputs was observed for the (p-TEA)(p-TEAH)PF6 devices even after exposure to 99% relative humidity, showcasing their utility under extremely humid conditions.
Keywords: 3D printing; cocrystals; energy harvesting; ferroelectricity; Piezoelectricity